Pivotal decade : how the United States traded factories for finance in the seventies - Stein, Judith, 1940-2017 (Yale University Press, 2010)
In this book, the author argues that in order to understand early twenty-first century economic crises, we need to look back to the 1970s and the end of the age of the factory - the era of postwar liberalism, created by the New Deal, whose practices, high wages, and regulated capital produced both robust economic growth and greater income equality. When high oil prices and economic competition from Japan and Germany battered the American economy, new policies - both international and domestic - became necessary. But war was waged against inflation, rather than against unemployment, and the government promoted a balanced budget instead of growth. This, says the author, marked the beginning of the age of finance and subsequent deregulation, free trade, low taxation, and weak unions that has fostered inequality and the worst recession in eighty years. Drawing on extensive archival research and covering the economic, intellectual, political, and labor history of the decade, the author provides a wealth of information on the 1970s. She also shows that to restore prosperity in the twenty-first century, America needs a new model: more factories and fewer financial houses. -- Publisher's description.